Crops and farmers’ response to application of fecal sludge derived - Fortifer™ in different agro-ecological zones in Ghana - Nartey, Eric Gbenatey; Cofie, Olufunke O.; Gebrezgabher, Solomie A.; Nikiema, Josiane (Elsevier, 2021)
Fecal sludge (FS)-derived fertilizer material, Fortifer™ was used in farmers’ field to cultivate different crops under varying soil and agro-climatic conditions in Ghana. The aim was to (1) create awareness among smallholder farmers for widespread use of Fortifer™ (2) observe the response of crops to Fortifer™ application by farmers in different agro-ecological zones (3) obtain farmers feedback on the FS-derived product to enhance further dissemination across the country. In total 95 farmers in six locations participated in the farmer-led pilots. Fortifer™ containing up to 3.0% nitrogen, 3.6% phosphorus, 1.3% potassium and 44.3% organic matter was applied to tomato, rice, maize and pepper in comparison to inorganic fertilizers at recommended rates. Subsequently, farmers’ perception of, and willingness to use the product were studied. Crop yield was significantly higher (p = 0.05) in the Fortifer™ plots compared to the inorganic fertilizer plots for all the selected crops. Yield was 12% higher for tomato, 27% for rice and maize and 30% for pepper under the Fortifer™ plots. Farmers indicated that, nutrient content was the most important factor they consider when making fertilizer purchasing decision.